Destination Branding in Relation to Airports: The Case of the City of Valencia - Vujicic, Sanja; Wickelgren, Mikael (European Journal of Transport and Infrastructure Research, 2011)
This study investigates various factors that contribute to the success of destination branding efforts where success is defined as the increase in airplane passenger numbers to a destination and its linked air transportation. Drawing on in-depth interviews and snowball sampling, the study examines the roles of many of the key actors involved in the efforts to increase passenger numbers. Using the City of Valencia in Spain as a case study, the role of its airport is examined as a factor of particular interest. The study concludes that Valencia has positioned itself among neighbouring destinations on the Spanish Mediterranean coast by its focus on high profile events and cultural tourism. However, other actors have taken a more active role in the effort to increase the number of tourists than the Valencia Airport that has taken a more passive role. Another finding is that the persistence in seeking resources for the costly branding efforts was another influential factor that explains the increase in Valencia tourism.